Religion and the Clinical Practice of Psychology.
DOI: 10.1037/10199-002
|View full text |Cite
|
Sign up to set email alerts
|

The psychology of religion: An overview.

Abstract: No other human preoccupation challenges psychologists as profoundly as religion. Whether or not they profess to be religious themselves-and many do not-psychologists must take religion into account if they are to understand and help their fellow human beings. Factoring in religion, however, is far more easily said than done, for in hardly any other sphere are individuals so cut off from one another. For modern secular psychologists, the great diversity of experiences, conceptions, and practices that constitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 3 publications
0
20
0
2
Order By: Relevance
“…Psychologists may be particularly prone to equate social deviance with psychopathology, since there is a general clinician bias to perceive psychopathology (Garb, 1998). As noted above, clinicians have frequently considered religious beliefs and behaviors to be symptoms of psychopathology -especially the socially deviant religious beliefs and behaviors which highly religious people demonstrate (Frame, 2003;O"Connor & Vandenberg, 2005;Wulff, 1996). It is true some socially deviant traits are also pathologically deviant.…”
Section: Religiousness Faith Magnitude and Psychopathologymentioning
confidence: 99%
“…Psychologists may be particularly prone to equate social deviance with psychopathology, since there is a general clinician bias to perceive psychopathology (Garb, 1998). As noted above, clinicians have frequently considered religious beliefs and behaviors to be symptoms of psychopathology -especially the socially deviant religious beliefs and behaviors which highly religious people demonstrate (Frame, 2003;O"Connor & Vandenberg, 2005;Wulff, 1996). It is true some socially deviant traits are also pathologically deviant.…”
Section: Religiousness Faith Magnitude and Psychopathologymentioning
confidence: 99%
“…But there is a body of evidence indicating that a questing orientation to religion, characterised by complexity, tentativeness and doubt, is more likely than orientations characterised by orthodoxy and commitment to be associated with such positive social traits as high levels of moral judgement, valuing of equality and non‐discriminatory attitudes (see Batson et al. 1993; Wulff 2001, p. 21). Thus, the lack of certainty in the spirituality of the holistic milieu may again be a sign of not weakness but maturity – or at least of a move towards maturity.…”
Section: Possibilities Of An Enduring Shared Culturementioning
confidence: 99%
“…This division has made arriving at a definition of religion difficult. Wulff (1996) discussed the theoretical differences that have contributed to modern psychology's understanding of religion. Several early theorists believed that religion was a liability.…”
Section: Religionmentioning
confidence: 99%
“…B.F. Skinner suggested that people engaged in religious practices because the practices were followed by reinforcing stimuli. He suggested that religious practices were essentially exploitative and aversive because their primary goal was to be controlling (Wulff, 1996). In addition to Skinner, Freud believed religion was an infantile response.…”
Section: Religionmentioning
confidence: 99%
See 1 more Smart Citation